2008
DOI: 10.1080/10934520802232006
|View full text |Cite
|
Sign up to set email alerts
|

Residue-response relationship between PAH body burdens and lysosomal membrane destabilization in eastern oysters (Crassostrea virginica) and toxicokinetics of PAHs

Abstract: This study was undertaken to establish residue-response relationship between lysosomal destabilization and body residues of multiple PAHs in eastern oysters (Crassostrea virginica) exposed to a mixture of PAHs for 25 days in laboratory aquariums. The contaminated oysters were then placed in clean aquariums for 20 days to allow them to depurate and recover. The lysosomal destabilization was linearly correlated with the PAH body burdens. Regression analysis showed that critical body residue (CBR), in terms of ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 38 publications
(29 reference statements)
5
10
0
Order By: Relevance
“…The observed PAH concentrations in the marine biota of the Kongsfjorden and Krossfjorden were well below threshold PAH concentrations for effects in marine species, as reported for Neanthes arenaceodentata (Hansen et al, 2003), Crassostrea virginica (Hwang et al, 2008) and Ruditapes philippinarum (Liu et al, 2014).…”
Section: Marine Biotasupporting
confidence: 57%
“…The observed PAH concentrations in the marine biota of the Kongsfjorden and Krossfjorden were well below threshold PAH concentrations for effects in marine species, as reported for Neanthes arenaceodentata (Hansen et al, 2003), Crassostrea virginica (Hwang et al, 2008) and Ruditapes philippinarum (Liu et al, 2014).…”
Section: Marine Biotasupporting
confidence: 57%
“…This critical body residue was exceeded only in 2 samples, 1 collected from AL‐D03‐A on 5 November and 1 collected from AL‐D02‐A on 13 November, suggesting that a potential reduction in feeding rate of mussels was of limited area and duration. Hwang et al reported that critical lysosomal destabilization started at 2100 ng/g (dry wt) of total PAHs in eastern oysters ( Crassostrea virginica ) and defined this concentration as a critical body residue, at which 50% of cells show destabilization. Assuming that this critical body residue in oysters is applicable to mussels without any conversion, PAHs in mussels collected from AL‐D02‐A, AL‐D02‐B, and AL‐D03‐A exceeded the critical body residue.…”
Section: Resultsmentioning
confidence: 99%
“…The lysosomal destabilization method used in the present study was a modification of the methods described by Lowe et al and Ringwood et al , as described by Hwang et al . Collected mussels were transported to the laboratory on the same day and stored in a refrigerator (4 °C) until the assay was performed the following day.…”
Section: Methodsmentioning
confidence: 99%
“…Lysosomal health has been traced in response to PAH-related stress as well. Lysosomes are organelles filled with hydrolytic enzymes and helpful to the detention of xenobiotics (reviewed by Hwang et al, 2008;Wang et al, 2018). Lysosomal enlargement in digestive cells occurred in crude oil HEWAF-exposed M. gigas (Luna-Acosta et al, 2017), potentially indicating storage of accumulated oil or PAHs.…”
Section: Histology and Physiologymentioning
confidence: 99%
“…Lysosomal enlargement in digestive cells occurred in crude oil HEWAF-exposed M. gigas (Luna-Acosta et al, 2017), potentially indicating storage of accumulated oil or PAHs. The lysosomes in hemocytes, however, were not only observed to increase in number in M. gigas exposed to DiBenzo[a,h]Anthracene (DBahA) (Bado-Nilles et al, 2008), but also experience membrane permeability in a process known as lysosomal destabilization in C. virginica exposed to a mixture of 24 PAHs and C. brasiliana exposed to a variety of chemicals including PAHs in coal tar-based paint (Hwang et al, 2008;Chiovatto et al, 2021). This membrane breach may result in the release of cathepsins into the cytoplasm (reviewed by Wang et al, 2018) that ultimately could be responsible for the hemocyte apoptosis recorded by Vignier et al (2018) in juvenile C. virginica exposed to crude oil HEWAF.…”
Section: Histology and Physiologymentioning
confidence: 99%